Materiality and organizing social interaction in a technological world - Leonardi, Paul M., 1979-; Nardi, Bonnie A.; Kallinikos, Jannis (Oxford : Oxford University Press, 2013)
This edited collection brings together leading academics in the field to explore the ways in which digital and non-digital artifacts shape how groups and collectives organize. It focuses on the idea of materiality and the interactions between the social and the technical in organizations, at work, and in technologies.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Computers -- Social aspects; Technological innovations -- Social aspects; Digital communications -- Social aspects; Organizational behavior